Silicon chemistry in the mesosphere and lower thermosphere. Issue 7 (14th April 2016) - Plane, John M. C.; Gómez‐Martín, Juan Carlos; Feng, Wuhu; Janches, Diego
Abstract: Silicon is one of the most abundant elements in cosmic dust, and meteoric ablation injects a significant amount of Si into the atmosphere above 80 km. In this study, a new model for silicon chemistry in the mesosphere/lower thermosphere is described, based on recent laboratory kinetic studies of Si, SiO, SiO2, and Si + . Electronic structure calculations and statistical rate theory are used to show that the likely fate of SiO2 is a two‐step hydration to silicic acid (Si(OH)4 ), which then polymerizes with metal oxides and hydroxides to form meteoric smoke particles. This chemistry is then incorporated into a whole atmosphere chemistry‐climate model. The vertical profiles of Si + and the Si + /Fe + ratio are shown to be in good agreement with rocket‐borne mass spectrometric measurements between 90 and 110 km. Si + has consistently been observed to be the major meteoric ion around 110 km; this implies that the relative injection rate of Si from meteoric ablation, compared to metals such as Fe and Mg, is significantly larger than expected based on their relative chondritic abundances. Finally, the global abundances of SiO and Si(OH)4 show clear evidence of the seasonal meteoric input function, which is much less pronounced in the case of other meteoric species. Key Points: Meteor‐ablated silicon should form silicic acid in the mesosphere A 3‐D model of Si chemistry predicts ion profiles in agreement with mass spectrometric measurements The meteor ablation rate of Si appears to be unexpectedly large compared to Fe and Mg